Acoustic parameter variation and emission patterns in franciscana dolphin (Pontoporia blainvillei) clicking behavior at high frequency - Bittencourt, Lis; Carvalho, Rafael R.; Pereira, Karina; Santos-Neto, Elitieri B.; Lailson-Brito, Jose; Bisi, Tatiana L.; Azevedo, Alexandre F. (Frontiers in Marine Science, 2025)
Franciscana dolphins are small odontocetes that produce narrow-band high-frequency echolocation clicks. Autonomous acoustic monitoring and field survey acoustic sampling were used to record franciscana dolphins in Ilha Grande Bay, Brazil. Clicking sequences were automatically detected and analyzed, and then manually classified into different types; acoustic parameters from individual clicks were extracted. A total of 12505 clicks were detected, 152 clicking sequences were analyzed, of which 43 were click trains and 109 were click packets. Considering all clicks, they occurred from 88.7 kHz to 250 kHz, with a mean peak frequency of 132.4 ± 6.8 kHz. Click trains were longer than click packets, with larger inter-click intervals and mean peak frequencies of 123.6 ± 16.4 kHz and 119.9 ± 15.0 kHz, respectively. Franciscana dolphins emitted different types of clicking sequences. The use of patterned clicks by franciscana dolphins may be an important communication feature at very high frequencies.